дидактические материалы алгебра 7 класс Звавич, Кузнецова

с-43

 

1. 1) a) (4a - b)(a - 6b) + a(25b - 3a) = 4a - 24ab - ab + 6b2 + 25ab - 3a2 = a2 + 6b2;
б) (2x + 3у)(х - у) - х(х + y) = 2x2 - 2ху + 3ху- 3y - x2 - xy = -x2 - 3y2;
в) 3а(а + 1) + (a + 2)(a - 3) = 3a2 + 3a + a2 - 3a + 2a - 6 = 4a2 + 2a - 6;
г) 2c(5c - 3) - (c - 2)(c - 4) = 10c2 - 6c - c2 + 4c + 2c - 8 = 9c2 - 8;
2) a)(3a + b)(a - 2b) + (2a + b)(a - 5b) = 3a2 - 6ab + ab - 2b2 + 2a2 - 10ab + ab - 5b2 = 5a2 - 14ab - 7b2;
б) (x + 1)(x + 7) - (x + 2)(x + 3) = x2 + 7x + x + 7 - x2 - 3x - 2x - 6 = 3x + 1;
в) (a - 4)(a + 6) + (a - 10)(a - 2) = a2 + 6a - 4a - 24 + a2 - 2a - 10a + 20 = 2a2 - 10a- 4;
г) (y - 3)(5 - y) - (4 - y)(y + 6) = 5y - y2 - 15 + 3y - 4y - 24 + y2 + 6y = 10y - 39.

2. 1) а) 3x(3x + 7) - (3x + 1)2 = 9x2 + 21x - 9x2 - 6x - 1 = 15x - 1;
б) 4b(3b + 6) - (3b - 5)(3b + 5) = 12b2 + 24b - 9b2 - 15b + 15b + 25 = 3b2 + 24b + 25;
2) а) (y - 2)(у + 3) - (y - 1)2 = y2 + 3y - 2y - 6 - y2 + 2y - 1 = 3y - 7;
б) (с - 5)(с - 1) - (с - 6)2 = с2 - с - 5с + 5 - с2 + 12с - 36 = 6с - 31;

3) а) (р + 1)2 - (р + 2)2 = р2 + 2р + 1 - р2 - 4p - 4 = -2p - 3;
б) (у - 4)2 - (4 - у)(4 + y) = y2 - 8у + 16 - 16 + у2 = 2y2 - 8у;
4) а) 4(а + 5)2 - (4а2 + 40а) = 4а2 + 40а + 100 - 4а2 - 40а = 100;
б) (4аb - b2) + 2(а - b)2 = 4аb - b2 + 2а2 - 4аb + 2b2 = 2а2 + b2.

3. a) (7 - x)(7 + x) + (x + 3)2 = 49 - x2 + x2 + 6x + 9 = 6x + 58;
6 • (-3,5) + 58 = 37;
6) (2a - b)2 - (2a + b)2 = (2a - b - 2a - b)(2a - b + 2a + b) =
= -2b(4a) = -8ab; -8 • 10/7 • 7/10 = -8;


4. 1) a) 3(2a - 5b)2 - 12(a - b)2 = 12a2 - 60ab + 75b2 - 12a2 + 24ab - 12b2 = 63b2 - 36ab;
6) 7(2a + 5)2 + 5(2a - 7)2 = 28a2 + 140a + 175 + 20a2 - 140a + 245 = 48a2 + 420;
2) а) (3x2 + 4)2 + (3x2 - 4)2 - 2(5 - 3x2)(5 + 3x2) = 9x4 + 24x2 + 16 + 9x4 -24x2 + 16 - 50 + 18x4 = 36x4 - 18;
6) (4a3 + 5)2 + (4a3 - 1)2 - 2(4a3 + 5)(4a3 - 1) = (4a3 + 5 - (4a3 - 1))2 = (6)2 = 36. (a2 - 2ab + b2 = (a - b)2);
3) a) (p - 2a)(p + 2a) - (p - a)(p2 + pa + a2) = p2 - 4a2 - p3 - p2a - pa2 + ap2 + a2p + a3 = a3 - p3 + p2 - 4a2;
6) x(2x - 1)2 - 2(x + 1)(x2 - x + 1) = 4x3 - 4x2 + x - 2x3 + 2x2 - 2х - 2х2 + 2х - 2 = 2x3 - 4х2 + х - 2.

5. 1) (2a - b)(2a + b) + (b - c)(b + c) + (c - 2a)(c + 2a) = 0;
4a2 - b2 + b2 - с2 + с2 - 4a2 = 0;
2) (3x + y)2 - (3x - y)2 = (3xy + 1)2 - (3xy - 1)2;
(3x + y - 3х + y)(3х + у + 3х - у) = (3ху + 1 - 3ху + 1)(3ху + 1 + 3xу - 1);
2у (6х) = 2(6ху); 12ху = 12ху - верно.